Swedish Forest Phenology dataset - Langvall, Ola (Swedish University of Agricultural Sciences, 2021)
As part of the SLU environmental monitoring and assessment program, the Experimental Forests of the university collect detailed phenological measurements and observations on the tree species downy birch (betula pubescens), silver birch (betula pendula), Norway spruce (picea abies) and Scots pine (pinus sylvestris), and on two berry shrubs common in the Swedish forest, bilberry (vaccinium myrtillus) and lingonberry (vaccinium vitis-idaea). The dataset includes detailed data on leaf and shoot development on the tree species, and on flowering, emergence of unripe and ripe berries on the berry species during the years 2006-2020. The dataset shows the averaged values of measurements and observations performed on several individuals during the same assessment day.

The dataset includes temperature sums, calculated from climate monitoring data performed at each observation site.

The dataset also includes R-scripts that read and handle the observation data tables by interpolation between assessment days and between temperature sum levels at assessments, to get estimated daily values and values for even steps of temperature sums, respectively. By this, daily averages and SE and temperature sum step averages and SE for all years can be calculated and plotted by the scripts.

Also, standard phenological phase shifts are observed on the birches (from bud burst to shedding of leaves), and on spruce and pine (only bud burst and shoot elongation).

Som en del av SLU:s fortlöpande miljöanalys, samlar universitetets skogliga försöksparker in detaljerade fenologiska mätningar och observationer på björk, gran, tall, blåbär och lingon, sedan 2006. Detta dataset innehåller data om löv- och skottutveckling hos träden, samt blomning, kartbildning och bärmognad hos bären för åren 2006-2020. I data redovisas medeltalet av ett flertal individer (se instruktion) som mätts eller observerats vid varje tillfälle.

Här tillhandahålls också temperatursummor, beräknade utifrån respektive observationsplats klimatstations dygnsmedeltemperaturer under samma tidsperiod.

Förutom mätvärden och observationer, tillhandahålls också R-script för att interpolera dagliga värden mellan observationstillfällena och för beräkningar av mellanårsmedelvärden och medföljande medelfel för varje observationsplats och art. R-scripten interpolerar även värden fördelade på uppnådd temperatursumma vid varje tillfälle, samt mellanårsmedelvärden och medelfel för temperatursummans utveckling över säsongen.

Även observationer av fenologiska fasförändringar görs på björk (från skottskjutning till lövfällning), samt tall och gran (endast skottskjutning) och finns i en separat tabell.
Svensk skogsfenologi - Svenskt skogsfenologidataset
Keywords: trees; träd; phenology; fenologi; berries; bär; ripening; bärmognad; shoot development; skottutveckling; flowering; blomning; bud burst; lövsprickning; Climate Science; Klimatvetenskap; Ecology; Ekologi; Forest Science; Skogsvetenskap; Environmental Sciences and Nature Conservation; Miljö- och naturvårdsvetenskap; Farming; Areella näringar; Biota; Biologi och ekologi